Expiratory Flow Limitation Definition, Mechanisms, Methods, and Significance - Claudio Tantucci (Pulmonary Medicine)
When expiratory flow is maximal during tidal breathing and cannot be increased unless operative lung volumes move towards total lung capacity, tidal expiratory flow limitation (EFL) is said to occur. EFL represents a severe mechanical constraint caused by different mechanisms and observed in different conditions, but it is more relevant in terms of prevalence and negative consequences in obstructive lung diseases and particularly in chronic obstructive pulmonary disease (COPD). Although in COPD patients EFL more commonly develops during exercise, in more advanced disorder it can be present at rest, before in supine position, and then in seated-sitting position. In any circumstances EFL predisposes to pulmonary dynamic hyperinflation and its unfavorable effects such as increased elastic work of breathing, inspiratory muscles dysfunction, and progressive neuroventilatory dissociation, leading to reduced exercise tolerance, marked breathlessness during effort, and severe chronic dyspnea.